ENTREPRENEURIAL ORIENTATION AFFECTS BUSINESS PERFORMANCE: A PERSPECTIVE FROM WOODCRAFTS MSMES IN JAKARTA - Zia, Nicholas; Utama, Louis (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to determine the effect of risk-taking, proactiveness, innovation, competitive aggressiveness, and Autonomy on the performance of woodcraft MSMEs. The population in this study are entrepreneurs who run MSMEs in woodcraft sector. The sample used in this study were 52 MSMEs entrepreneurs in the woodcraft center at the Outer Ring Road of Jakarta W1 (West Jakarta) and Pahlawan Revolusi Street (East Jakarta). The type of sampling technique used was judgmental sampling. Data collection was done using a questionnaire distributed to entrepreneurs who were willing to become respondents then the data obtained will be processed using SmartPLS 3.0 software. The results of this study point out that risk-taking, proactiveness, and Autonomy have a positive effect on the performance of MSMEs in the woodcraft center on the Outer Ring Road of Jakarta W1 (West Jakarta) and Pahlawan Revolusi Street (East Jakarta), while for innovation and competitive aggressiveness there was no influence on the performance of MSMEs in the woodcraft center on the Outer Ring Road of Jakarta W1 (West Jakarta) and Pahlawan Revolusi Street (East Jakarta).